Sudden Infant Death Syndrome and Forensic Nursing Approach - Yıldız, İlknur (The Bulletin of Legal Medicine, 2018)
Sudden infant death syndrome (SIDS), is a sudden death of infants under one year of age with no health problems and unexplained autopsy. The frequency of SIDS in the world varies according to societies. SIDS may develop due to developmental, environmental and biological risk factors. Preterm birth of infant, mother’s tobacco use, bed-sharing and prone sleeping position are some of the factors that increase the SIDS risk the risk of. In the case of suspected SIDS cases that require further investigation and evaluated within the scope of the forensic case, the educated forensic nurses in the forensic medicine to be included in the research team has an important role in the evaluation and resolution of the case. The forensic nurse should explain to the parents that the questions in the interviewing are designed to gather information and determine risk factors, not accuse the parents. Parents have difficulty in accepting the death of their baby and experience stress, anger and guilt. In this context, it should be allowed to express the feelings of the family, to explain that death is not is not the result of their own fault and to reduce family’s guilt feelings.
Keywords: Sudden Infant Death Syndrome; Forensic Nursing; Parent